2008
DOI: 10.1890/07-1671.1
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Effects of an Exploited Predator on Recruitment of Coral-Reef Fishes

Abstract: The more ecologists examine the role of trait-mediated indirect interactions (TMIIs), especially in regulating predator-prey interactions, the more we recognize their fundamental role in structuring food webs. However, most empirical evidence for TMIIs comes from studies that are either conducted in laboratory or mesocosm venues or are restricted to simple food webs involving lower trophic-level animals. Here, I quantified the direct and indirect effects of interactions between high-level vertebrate predators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
122
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 32 publications
5
122
0
Order By: Relevance
“…One interpretation of these patterns of species' responses to the reserve is that large predators such as sharks, barracuda, and large grouper inside the marine reserve likely reduced the biomass of smaller predatory fishes such as snapper and smaller grouper. Although we did not study trophic interactions directly, such interactions have been empirically demonstrated in the Bahamas (Eggleston et al 1998, Stallings 2008. The lowered biomass of midsize predators in turn appeared to reduce the amount of predation on their prey, resulting in an increase in relative biomass in some of the smaller planktivorous and carnivorous species.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…One interpretation of these patterns of species' responses to the reserve is that large predators such as sharks, barracuda, and large grouper inside the marine reserve likely reduced the biomass of smaller predatory fishes such as snapper and smaller grouper. Although we did not study trophic interactions directly, such interactions have been empirically demonstrated in the Bahamas (Eggleston et al 1998, Stallings 2008. The lowered biomass of midsize predators in turn appeared to reduce the amount of predation on their prey, resulting in an increase in relative biomass in some of the smaller planktivorous and carnivorous species.…”
Section: Discussionmentioning
confidence: 83%
“…For example, in addition to direct consumption, large predatory species can also have non-lethal, negative effects on the biomass of smaller fishes. In the Bahamas, large groupers may out-compete smaller groupers for food and/or territory, causing a reduction in growth rates of small groupers (Stallings 2008). Growth rates can also be reduced when prey species choose inferior habitats in a tradeoff with predator avoidance (Werner et al 1983).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations